Personality Traits, Sedentariness, and Personal Dilemma as the Dynamic Predictors of Intention to Use Public Transportation in Greater Jakarta - Abraham, Juneman; Wirayudha, Muhammad Sahid (UI Scholars Hub, 2015)
The management of mass public transportation requires the psychology of transportation in order to design and operate a transportation system which suits the social psychology dimension of urban citizens. The aim of this research is to examine the role of personality traits, sedentariness, and personal dilemma in predicting the intention of a particular group of urban citizens to switch from using private cars to using mass public transportation. This research uses the predictive correlational design, while the research data are analyzed using the multiple linear regression technique in order to identify the main effects and interaction effects of variables which may serve as the predictors of intention. This research involves 280 university students (111 males and 169 females, with Mage = 20.90 years old and SDage = 1.943 years old) who live in Jakarta, the capital city of Indonesia, and its surrounding urban areas as samples. The research finds that, among the Big Five personality traits, conscientiousness is the only trait which can significantly predict the intention of private car users, while sedentariness is not capable of predicting such intention. The research also finds that losses in terms of time and safety incurred from the use of private cars can lead to a much stronger intention to switch to mass public transportation. The implications of this research on the development of policies regarding transportation are elaborated in the final section of this paper.